PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DAN ANAK DARI TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA : (Pendampingan, Konseling, Advokasi dan Sosialisasi Hukum di Desa Labuhan Ratu IX Kecamatan Labuhan Ratu Kabupaten Lampung Timur) - Permatasari, Ermanita (Jurnal Peduli : Jurnal Pengabdian Kepada Masyarakat, 2021)
Domestic violence is a form of violence based on the usual assumptions about gender regarding the relationship between men and women. Domestic violence stems from a wrong perspective, namely that human dignity and standardization of gender roles in a person are underestimated. Violence against women and children is not only found in physical violence but psychological and economic violence. The purpose of this service is to provide information to the public, especially in Labuhan Ratu IX Village, Labuhan Ratu District, East Lampung Regency, Lampung Province that women and children have been given protection to the state through legislation, one of which is Law no. 23 of 2004 concerning the Elimination of Domestic Violence and Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection. The method used in this service is PAR (Participatory Action Research) which emphasizes the problems faced by the community by providing assistance, Mentoring, Counseling, Advocacy and Socialization on the Law on criminal acts of domestic violence and protection of minors. The result of this service activity is to provide an understanding to the community about domestic violence. The purpose of this service is so that the community can prevent the occurrence of domestic violence in the future.